(untitled) (Scientific journal of the Fergana State University, 2024)
Digital data overwriting is the process of eliminating evidence in a digital environment. Many computer users are now aware of the risks associated with recovering their files after they have been deleted. As a result, they prefer to overwrite their files rather than simply delete them to prevent any unwanted searches. Although there are specialized tools available that can successfully recover data deleted using non-traditional methods, they are expensive and require skilled technical personnel. To effectively manage digital evidence in various scenarios, it is important to use a variety of tools instead of relying on just one technology or method. This study has shown that using non-traditional methods for deleting digital data can be an effective way to destroy data.The aim of this research was to assess the efficiency of open-source tools in retrieving deleted data through unconventional methods.